3D CoSe@C Aerogel as a Host for Dendrite‐Free Lithium‐Metal Anode and Efficient Sulfur Cathode in Li–S Full Cells. Issue 41 (22nd September 2020) - He, Jiarui; Manthiram, Arumugam
Abstract: Lithium–sulfur batteries are appealing due to their high energy density and low cost. However, their commercial viability is challenged by uncontrollable dendritic Li growth and severe polysulfide shuttling during cycling. Here, a 3D framework coupling lithiophilic and catalytic CoSe nanoparticles with conductive carbon nanowires (CoSe@C) as an efficient host both for lithium and sulfur is reported. As a cathode host, CoSe@C offers highly efficient catalytic activity for polysulfide redox. As a rationally designed matrix with a high affinity for Li, CoSe@C guides a homogenous growth of Li within the 3D framework, which effectively suppresses dendritic Li growth. As a result, the CoSe@C/Li anode exhibits an ultralong lifespan of > 3000 h with a low overpotential of <23 mV. Remarkably, a full cell with a S/CoSe@C cathode and a CoSe@C/Li anode with a low negative to positive electrode capacity (N/P) ratio of ≈4 exhibits long cycle life of over 600 cycles with a high areal capacity of 5.8 mA h cm −2 . It also remains stable after 50 cycles even with lean electrolyte (E/S: 4.5 µL mg −1 ) and a low N/P ratio of ≈4. This work offers new insights and opportunities for developing dendrite‐free, high‐performance Li–S battery technology. Abstract : A 3D framework constructed of CoSe‐decorated carbon nanowires is demonstrated as a dendrite‐free metallic Li host to overcome the challenges of Li‐metal anodes. Benefiting from the lithiophilic and catalytic properties of the CoSe@C host, the Li–S full cell of S/CoSe@C||CoSe@C/Li exhibits a long cycle life of over 600 cycles and a high areal capacity of 5.8 mA h cm −2 .